Working Professionals and Subject Matter Experts in the Classroom - David A Line; Stephen F Pyle (Academic Chairpersons Conference Proceedings, 2017)
Integrating real world expertise is a positive and growing trend in higher education. Building positive relationship with working professionals and subject matter experts has benefits and pitfalls. This session explores the pros and cons of using working professionals and subject matter experts in the classroom and in course development.
Keywords: Working Professionals Subject Matter Experts